(untitled) (Proceedings of Southern Federal University. Philology, 2020)
The article is devoted to the study of precedent units with the source «ancient Greek mythology», which have the potential to broadcast the linguistic and cultural features of a particular community, the recognition of which influences the success of intercultural communication. The work provides a comprehensive analysis of the precedent units included in the cycle «The History of the Golden Fleece», namely «Argonauts», «Golden Fleece», «Jason» in the texts of Russian-language media. In the article the author argues that the change in the semantics of constructions occurs not only at the denotative, but also at the connotative, pragmatic level, where the studied precedent units acquire new semantic features. The analysis of the functioning features of the precedent units included in the «History of the Golden Fleece» cycle allows us to establish the linguistic mechanisms of their «deployment» in the media discourse and come to the conclusion about the specifics of the fragment of the worldview, fixed in mythologized precedent phenomena. Key words: precedent unit, precedent situation, ancient Greek mythology, golden fleece, Argonauts, media discourse. DOI 10.18522/1995-0640-2020-4-107-114